AB0217 Relationship between anti-ccp positivity, results of pulmonary function tests and high resolution computed tomography of the lung in patients with rheumatoid arthritis. (23rd January 2014) - Bestaev, D.; Karateev, D.; Bozhjeva, L.; Nasonov, E.
Abstract : Background: Interstitial lung disease (ILD) represents a severe manifestation in connective tissue diseases, and is it still a challenge for clinicians evaluation and management. ILD is the most common manifestations of lung involvement in rheumatoid arthritis(RA), observed in up to 80% of biopsies, 50% of chest computed tomography and only 5% of chest radiographs. Objectives: The aim of this study was to investigate the pulmonary high resolution computed tomography (HRCT) findings of patients with RA, and to determinate the relationship between pulmonary function tests (PFT), HRCT findings and some disease parameters. Methods: A total of 69 patients (61 female, 8 male) with definite RA were enrolled in the study. The mean age was 52, 6±12, 4 years (range 25-81), mean disease duration was 10, 7±8, 6 years (range 0, 25-40). None of the patients was smoker. The physical examination, PFT, diffusing lung capacity (DLC), chest HPCT (GE "Light Speed VCT), laboratory analysis (rheumatoid factor (RF), antiCCP (cyclic citrullinated peptid) antibody, full blood count, ESR, C-reactive protein (CRP-hs) were performed in each subject. Disease activity was assessed by DAS28. HCRT scans categorized into presence or absence of ground glass opacification, honeycombing, fibrosis, rheumatoid nodules, interlobular or intralobular interstitial thickening, traction bronchiectasis. Results: HCRT of the lung disclosed abnormalities in 58/69 (84, 1%) patients. The most frequent pathologic signs were fibrosis (58, 6% pts), followed by ground glass opacification (10, 4%) and honeycombing (3, 6%). 27, 5% patients had mixed pattern of HCRT abnormalities. Some parameters of RA patients with (n=58) and without (n=11) ILD are listed in table 1 . There were not significant differences in age, disease duration, disease activity, presence of extraarticular RA manifestations and some respiratory symptoms between groups of patients with and without ILT as revealed by HCRT. ACCP levels was significantly higher (p<0, 05) in patients with ILD compared to pts without ILD. All patients with HCRT pattern of ground glass opacification (n=6) had high positive ACCP. Mean disease activity (DAS28) in this subgroup was 5, 2 ± 0, 63; decrease of DLC % predicted was 59, 9±2, 1%. Patients with ground glass opacification demonstrated inverse correlation between ACCP levels and DLC (r=-0, 42, p<0, 05). Conclusions: We observed high frequency of HCRT abnormalities in RA patients significantly associated with ACCP positivity. High titers of ACCP antibody in patients with pattern of ground glass opacification may suspect as marker active lung involvement. Our results suggest pathogenic role of ACCP in development interstitial lung disease in RA. References: Bongartz T, Nannini C. Incidence and mortality of interstitial lung disease in rheumatoid arthritis: a population-based study. Disclosure of Interest: None Declared